The Role of Islamic Religious Education in Strengthening the Faith, Manners and Character of Students at Kuttab Ibnu Abbas Karanganyar - Sanusi, M.; Sukari, Sukari (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
The strengthening of faith, manners, and character in students is an urgent matter for today's learners. The purpose of this research is to describe the reinforcement of faith, manners, and character of students through Islamic education at Kuttab Ibnu Abbas Karanganyar. This study is a type of field research. The research approach used is a qualitative descriptive approach, addressing the issues found. To obtain valid data to support the research, this study applies observation, interviews, and documentation methods in data collection. The data analysis technique uses the Milles Hubberman approach, which includes data reduction, data display, and drawing conclusions. The results of the research at Kuttab Ibnu Abbas Karanganyar show that: 1) Islamic education plays a crucial role in strengthening the faith, manners, and character of students; 2) The implementation of a well-planned, organized, and systematic Islamic education learning process has proven to support the reinforcement of students' faith, manners, and character; 3) The integration of Islamic values into general subjects, extracurricular activities, and skills is a supporting factor in the success of Islamic education, which impacts the strengthening of students' faith, manners, and character; 4) Faith, manners, and character are the main and essential variables in realizing the goals of national education and Islamic education simultaneously.